The recurrent causal mutation for osteogenesis imperfecta type V occurs at a highly methylated CpG dinucleotide within the IFITM5 gene - Corradi, Massimiliano; Monti, Elena; Venturi, Giacomo; Gandini, Alberto; Mottes, Monica; Antoniazzi, Franco (Journal of Pediatric Genetics, 2014)
Recent studies have identified the molecular defect underlying autosomal dominant osteogenesis imperfecta (OI) type V. Unlike all other OI types, which are characterized by high genetic heterogeneity, OI type V appears consistently associated to a unique de novo C>T transition within the 5′ UTR of the IFITM5 gene. Although the precise frequency of OI type V is not known, this recurrent base substitution may well represent a mutational hotspot in the human genome. We show that it occurs at a CpG dinucleotide that is highly methylated in several tissues and particularly in the sperm DNA, suggesting a mutational mechanism common to other de novo recurrent dominant mutations.
Keywords: Osteogenesis imperfecta; IFITM5; DNA methylation; CpG dinucleotide deamination